INTEGRASI ISLAM DAN SAINS DALAM PERSPEKTIF AL-QUR’AN: RELEVANSI PARADIGMA KEILMUAN AMIN ABDULLAH DI ERA POST-TRUTH - Helga Juliya; Sawaluddin Siregar (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This article examines the new scientific paradigm offered by M. Amin Abdullah in the context of dialogue between Islam and science in the post-truth era. The background of this research departs from the dichotomy of religious science and general science which results in stagnation in the development of Islamic science in higher education. Through a qualitative approach with the literature study method, this study examines the works and thoughts of M. Amin Abdullah related to the integration-interconnections of knowledge known as the